Zonisamide Ameliorates Cognitive Impairment by Inhibiting ER Stress in a Mouse Model of Type 2 Diabetes Mellitus - He, Yong-Xiang; Shen, Qi-Ying; Tian, Jia-Hui; Wu, Qian; Xue, Qin; Zhang, Gui-Ping; Wei, Wei; Liu, Ying-Hua (Frontiers in Aging Neuroscience, 2020)
Type 2 diabetes mellitus (T2DM) increases the risk of Alzheimer's disease (AD)-like dementia and pathology. Endoplasmic reticulum stress (ERS) plays a key role in the development of cognitive impairment in T2DM. Zonisamide (ZNS) was found to suppress ERS–induced neuronal cell damage in the experimental models of Parkinson's disease. However, the protective effect of Zonisamide in the treatment of diabetes-related dementia is not determined. Here, we studied whether ZNS can attenuate cognitive impairments in T2DM mice. C57BL/6J mice were fed with a high-fat diet and received one intraperitoneal injection of streptozotocin to develop T2DM. After the 9-week diet, the mice were orally gavaged with ZNS or vehicle for 16 consecutive weeks. We found that ZNS improved spatial learning and memory ability and slightly attenuated hyperglycemia. In addition, the expression levels of synaptic-related proteins such as post synaptic density 95 (PSD95) and synaptophysin, were increased along with the activation of the cyclic AMP response element-binding (CREB) protein and cAMP-dependent protein kinase (PKA) both in hippocampus and cortex of T2DM mice. Meanwhile, ZNS attenuated A deposition, tau hyperphosphorylation at Ser-396/404, and also decreased the activity of tau upstream kinases including extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK). Moreover, ZNS also decreased the ERS hallmarks protein levels. These data suggest that ZNS can efficiently prevent cognitive impairment and improve AD-like pathologies by attenuating ERS in T2DM mice.